X

Available for CBSE, ICSE and State Board syllabus.

Call our LearnNext Expert on 1800 419 1234 (tollfree)

OR submit details below for a call back

Rajesh kumar pandey

Aug 8, 2013

If the roots of the equation (a-b)x^{2} + (b-c)x + (c-a) = 0 are equal , the prove 2a=b+c.

Given quadratic equation (a-b)x^{2} + (b-c)x + (c-a)=0

If the quadratic equation ax^{2 }+ bx + c has equal roots then its discriminant is equal to ...

If the quadratic equation ax

Brajesh kedia Kedia

Mar 29, 2013

Solve the equation:-a/x-b + b/x-a = 2Answer:-x=a+b or a+b/2[nOTE:-Please give all the solution possible on this Question as i am not able to solve in my way..

This answer has an image. Please click on the question to read more.

Nandini thanga raj

Mar 23, 2014

n^{2}+301n-12132 = 0

This answer has an image. Please click on the question to read more.

Niharika Bagri

Nov 4, 2014

A farmer prepares a rectangular vegetable garden of area 180 sq metres.With 39 metres of barbed wire, he can fence the three sides of the garden ,leaving one of the longer sides unfenced. Find the dimensions of the garden.

Sol:

Area of the rectangle = 180 cm^{2}

Let the length of the rectangle be 'l' m and breadth be 'b' m.

Three sides of the garden are fenced with 39 m of wire.

Kapil

Feb 27, 2014

Solve for x : (2x-7)(x^{2}-9)(2x+5)=91

Sol :

Post the question properly.

Post the question properly.

Fransis

Feb 14, 2014

1/(x-1) - 2/(x-2) = 3/(x-3) - 4/(x-4)

Sol :

Given 1/(x-1) - 2/(x-2) = 3/(x-3) - 4/(x-4)

â‡’ (x-2) - 2(x-1) / (x-2)(x-1) = 3(x-4) - 4(x-3) / (x-3)(x-4)

â‡’ -x / (x^{2}-3x+2) = -x / (x^{2}-7x+12)

&#...

Given 1/(x-1) - 2/(x-2) = 3/(x-3) - 4/(x-4)

â‡’ (x-2) - 2(x-1) / (x-2)(x-1) = 3(x-4) - 4(x-3) / (x-3)(x-4)

â‡’ -x / (x

&#...

Apoorva

Jan 2, 2014

How to find sqaureroot of a no., if we have to find it nearest to 4 decimal points. Eg, 89 ???

This answer has an image. Please click on the question to read more.

Uttam mazumder

Oct 3, 2014

Solve the equation by reducing it to quadratic equation 2^{2x+3}+2^{x+3}=1+2^{x}

Sol:

Given 2^{2x+3} + 2^{x+3} = 1 + 2^{x}

Let 2^{x} = t

â‡’ (2^{x})^{2} Ã— 2^{3}+ (2^{x})Ã— 2

Given 2

Let 2

â‡’ (2

Rajesh kumar pandey

Aug 8, 2013

If the roots of the equation (a-b)x^{2} + (b-c)x + (c-a) = 0 are equal , the prove 2a=b+c.

Given quadratic equation (a-b)x^{2} + (b-c)x + (c-a)=0

If the quadratic equation ax^{2 }+ bx + c has equal roots then its discriminant is equal to ...

If the quadratic equation ax

Brajesh kedia Kedia

Mar 29, 2013

Solve the equation:-a/x-b + b/x-a = 2Answer:-x=a+b or a+b/2[nOTE:-Please give all the solution possible on this Question as i am not able to solve in my way..

This answer has an image. Please click on the question to read more.

Nandini thanga raj

Mar 23, 2014

n^{2}+301n-12132 = 0

This answer has an image. Please click on the question to read more.

Niharika Bagri

Nov 4, 2014

A farmer prepares a rectangular vegetable garden of area 180 sq metres.With 39 metres of barbed wire, he can fence the three sides of the garden ,leaving one of the longer sides unfenced. Find the dimensions of the garden.

Sol:

Area of the rectangle = 180 cm^{2}

Let the length of the rectangle be 'l' m and breadth be 'b' m.

Three sides of the garden are fenced with 39 m of wire.

Kapil

Feb 27, 2014

Solve for x : (2x-7)(x^{2}-9)(2x+5)=91

Sol :

Post the question properly.

Post the question properly.

Fransis

Feb 14, 2014

1/(x-1) - 2/(x-2) = 3/(x-3) - 4/(x-4)

Sol :

Given 1/(x-1) - 2/(x-2) = 3/(x-3) - 4/(x-4)

â‡’ (x-2) - 2(x-1) / (x-2)(x-1) = 3(x-4) - 4(x-3) / (x-3)(x-4)

â‡’ -x / (x^{2}-3x+2) = -x / (x^{2}-7x+12)

&#...

Given 1/(x-1) - 2/(x-2) = 3/(x-3) - 4/(x-4)

â‡’ (x-2) - 2(x-1) / (x-2)(x-1) = 3(x-4) - 4(x-3) / (x-3)(x-4)

â‡’ -x / (x

&#...

Apoorva

Jan 2, 2014

How to find sqaureroot of a no., if we have to find it nearest to 4 decimal points. Eg, 89 ???

This answer has an image. Please click on the question to read more.

Uttam mazumder

Oct 3, 2014

Solve the equation by reducing it to quadratic equation 2^{2x+3}+2^{x+3}=1+2^{x}

Sol:

Given 2^{2x+3} + 2^{x+3} = 1 + 2^{x}

Let 2^{x} = t

â‡’ (2^{x})^{2} Ã— 2^{3}+ (2^{x})Ã— 2

Given 2

Let 2

â‡’ (2